Crosstalk between substance P and calcitonin gene‐related peptide during heterotopic ossification in murine Achilles tendon. Issue 5 (5th January 2018) - Tuzmen, Ceren; Verdelis, Kostas; Weiss, Lee; Campbell, Phil
ABSTRACT: Heterotopic ossification (HO) is abnormal bone formation within soft tissue, usually predisposed by neurogenic or musculoskeletal trauma. Inflammation resulting from trauma is considered to be the main trigger for HO by eliciting changes within the injury site, including elevation of bone morphogenetic proteins (BMPs). Recent research, however, has also associated changes in sensory neuropeptide expression with HO. Substance P (SP) and calcitonin gene‐related peptide (CGRP) are two of those neuropeptides that have been implicated with various aspects of HO, including regulation of inflammation and BMP signaling. Despite discoveries associating SP and CGRP with soft tissue HO, it remains unclear whether SP and CGRP have a direct role in the induction of HO. Here, we investigated the effect of SP and CGRP in vivo with the aid of inkjet‐based biopatterning technology to controllably deliver these neuropeptides onto a murine Achilles tendon. While we did not observe any significant effect with CGRP, SP alone promoted HO in vivo with increased expression of BMP2. Remarkably, when SP and CGRP were delivered together, CGRP counteracted the effect of SP and essentially blocked SP‐induced HO. This report contributes to the understanding of the complex problem of HO pathophysiology and warrants more study to better elucidate the interplay between SP and CGRP in the induction of HO. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1444–1455, 2018.